Life History of Spodoptera exigua (Lepidoptera: Noctuidae) on Various Host Plants - Azidah, A.A.; Sofian-Azirun, Mohd (2006)
The incubation period of Spodoptera exigua (HÃ¼bner) was not influenced by the host plant, whereas larval development time and pupal period were affected. Larval development time was longest on shallot and lady's finger, followed by cabbage and long bean. Larvae did not develop beyond the first instar when fed on chilli. The pupal period was longer on lady's finger than on cabbage, shallot and long bean. Overall, adult longevity was not influenced by the host plant but there was a difference between female and male longevity among the host plants. Survival of S. exigua was affected by the host plant at the larval stage. The number of larval instars varied between 5 and 8 within and between the studied host plants. Long bean was found to be the most suitable host plant and provide the best food quality for S. exigua compared to the other host plants, as it allowed faster development, fewer larval instars and a higher survival rate. Â© 2006 Cambridge University Press.